Characterization and dielectric properties of pure and er-substituted Bi₄Ti₃O₁₂ and Bi₅CrTi₃O₁₅ aurivillius ceramics - Wong, Yick Jeng (2018)
Aurivillius compounds, (Bi₂O₂)²+(Bin-1TinO3n+1)², are structurally constructed by alternately stacking n perovskite units of (Bin-1TinO3n+1)2 with two fluorite-like layers of (Bi₂O₂)2+. Three-layered Bi₄Ti₃O₁₂ system in this kind of compounds is extensively studied. In most cases, the modification is done by doping various types of rare-earth ions at Bi-site to reduce high electrical conductivity for more effective ferroelectric dielectrics. Unlike the three-layered Aurivillius systems, attention to the four-layered Aurivillius systems isostructural with Bi₅FeTi₃O₁₅ is scarce, especially Bi₅CrTi₃O₁₅. Such a case involving the magnetic Cr3+ ions was only reported from the analysis of powder neutron diffraction data. Preparation of the Aurivillius compounds is commonly done by conventional solid state reaction method. However, this economical method requires high-temperature solid state reaction to reach single phase. Here, high energy milling at room temperature for the mechanosynthesis of Aurivillius compounds with Bi₄Ti₃O₁₂, Bi₃.₂₅Er₀.₇₅Ti₃O₁₂, Bi₅CrTi₃O₁₅, and Bi₄.₂₅Er₀.₇₅CrTi₃O₁₅ compositions is employed. These mechanosynthesized samples subjected to a range of sintering temperatures (700 – 1000oC) are systematically compared with the conventionally processed samples in terms of X-ray Diffraction (XRD) analysis, Field Emission Scanning Electron Microscopy (FE-SEM) observation, dielectric, and density measurements. All the comparative results obtained point to the effectiveness of the high energy milling over the conventional processing technique as a more efficient solid-phase formation method in synthesizing the studied samples. This is first demonstrated by room-temperature XRD studies. The sintering temperature at which these mechanosynthesized compounds show complete formation of the pure phase are comparatively lower than those of conventionally processed samples as a result of the mechanochemical reaction by high energy milling.Consequently, FE-SEM observations of the mechanosynthesized samples reveal distinct grain morphologies contrary to the plate-like grain morphologies in the conventionally processed samples, in which the latter display grain growth with increasing sintering temperature controlled by anisotropic grain boundary. For the mechanosynthesized Bi₄Ti₃O₁₂, triple junction controlled grain growth is evident, while the grain growth of mechanosynthesized Bi₄.₂₅Er₀.₇₅CrTi₃O₁₅ is discovered for the first time being governed via multiple ordered coalescence of nanocrystals. Also, the mechanochemical effect triggers the improved sintered densities in the mechanosynthesized samples. For this reason, the mechanosynthesized samples exhibit much higher room-temperature dielectric constant values in the frequency range of 100 Hz – 10 MHz. All samples prepared by both methods exhibit common feature in the variation of dielectric constant with respect to frequency, which follows directly from the relationship between densification and sintering temperature. Moreover, very similar intrinsic frequency dispersion of dielectric responses could be observed, with the physical basis for the interpretation is based on the empirical fitting model of relaxation functions: Cole-Cole, Cole-Davidson, and Havriliak-Negami. Besides comparison of methods, the influence of Er3+ dopant on the parent structure of Bi₄Ti₃O₁₂ and Bi₅CrTi₃O₁₅ is also investigated. The marked contributions of this dopant are from the grain growth inhibition due to the grain boundary segregation of Er3+ and weak low-frequency dispersion of the dielectric constant in the doped samples. These experimental evidences reflect the suppression of oxygen vacancies, which is also manifested in one of the fitting parameters, the reduced direct current conductivity.